A case report of acute pulmonary hypertension after hyperthermic intraperitoneal chemotherapy (HIPEC) and review of the literature. (March 2018) - Zajonz, Thomas S.; Sander, Michael; Padberg, Winfried; Hecker, Andreas; Hörbelt, Ruediger; Koch, Christian; Schneck, Emmanuel
Abstract: Background: Hyperthermic intraperitoneal chemotherapy (HIPEC) poses a widely used and accepted treatment option for patients with peritoneal carcinomatosis of gastrointestinal tumors. In contrast to the well-described risks and complications of intravenous cytostatic drugs, literature offers only scarce information of serious complications following HIPEC. To our knowledge no other description of rapid progressive pulmonary hypertension (PH) and consecutive respiratory failure following HIPEC have been described in current literature. Case presentation: A 48-year-old female suffering from a recurrent appendix-carcinoma developed progressive dyspnea and fatigue six weeks after multivisceral abdominal resection and HIPEC. Medical examinations included laboratory-checks, non-invasive imaging, scintigraphy as well as invasive examinations (left-/right-heart-catheterization) and confirmed PH of unknown origin to be the cause of dyspnea. The patient died nine days after admission of respiratory failure and rapid deterioration as a result of aggravating PH. Conclusion: Rapid progressive respiratory insufficiency due to PH following HIPEC procedure might represent a rare complication, but must be considered because of the high clinical impact. Further studies are necessary to investigate the correlation between HIPEC and PH. Highlights: We report a fatal case of rapid progress of pulmonary hypertension after Oxaliplatin-containing HIPEC therapy. Oxaliplatin is the most likely cause of pulmonary damage leading to PH in the presented patient. Oxaliplatin-induced interstitial lung diseases should be regarded in respiratory disorders following HIPEC procedure. Further investigations of chemotherapeutical-induced side effects on the respiratory system after HIPEC are necessary.